2021
DOI: 10.1101/2021.08.10.21261834
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Immuno-proteomic profiling reveals abundant airway CD8 T cells and ongoing epithelial injury in prolonged post-COVID19 respiratory disease

Abstract: Some patients hospitalized with acute COVID19 suffer respiratory symptoms that persist for many months. To characterize the local and systemic immune responses associated with this form of long COVID, we delineated the immune and proteomic landscape in the airway and peripheral blood of normal volunteers and patients from 3 to 6 months after hospital discharge. The bronchoalveolar lavage (but not peripheral blood) proteome was abnormal in patients with post-COVID19 lung disease with significantly elevated conc… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 59 publications
2
17
0
Order By: Relevance
“…The acute effects of SARS-CoV-2 are mainly marked by dysregulation of inflammatory markers and complement factors, as has been described before ( 9 , 35 ). Consistent with earlier research in COVID-19 patients after the infection phase ( 12 ), our results suggest that a substantial proportion of proteins (109/220, ~50%) return to normal levels as they do not show statistical difference compared to controls in the post-infection phase. A note of caution for this conclusion is that we cannot completely exclude that for some proteins this may be caused by other factors such as a lack of statistical power to detect differences.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The acute effects of SARS-CoV-2 are mainly marked by dysregulation of inflammatory markers and complement factors, as has been described before ( 9 , 35 ). Consistent with earlier research in COVID-19 patients after the infection phase ( 12 ), our results suggest that a substantial proportion of proteins (109/220, ~50%) return to normal levels as they do not show statistical difference compared to controls in the post-infection phase. A note of caution for this conclusion is that we cannot completely exclude that for some proteins this may be caused by other factors such as a lack of statistical power to detect differences.…”
Section: Discussionsupporting
confidence: 92%
“…Taken together, there is an urgent need for understanding the mechanisms underlying COVID-19 and establishing biomarkers for patient stratification, to be able to identify patients who will progress to severe disease or take more time to recover. Targeted proteomics has proven successful in identifying key mediators of disease, also in COVID-19 ( 7 12 ). However, most of these studies are confined to smaller sample sizes, and few studies include individuals after the initial phase of the disease.…”
Section: Introductionmentioning
confidence: 99%
“…Our data suggests that this transition may be delayed in severe COVID19 since pro-in ammatory signatures remained elevated compared to mild disease. This is supported by other studies in the literature that have shown increased systemic in ammation-associated markers in individuals recovering from acute severe COVID19 when compared to healthy control subjects 17,28 .…”
Section: Discussionsupporting
confidence: 87%
“…Having identi ed persistent immune activation following severe COVID19, we sought to determine whether components of this pro-in ammatory signature, or alternative pathways, are selectively upregulated in subjects with persistent morphologic abnormalities following COVID-19 compared to those showing radiographic resolution. Such comparisons have the potential to offer clearer discrimination of key mechanistic drivers than comparisons to healthy uninfected subjects, as has been the case in other studies 17,18 . The present study has identi ed a range of selectively increased plasma proteins in individuals with post-COVID interstitial lung changes predominantly consistent with a neutrophil-associated in ammatory signature.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation